Atlas of ultrasound- guided regional anesthesia - Gray, Andrew T. (Elsevier/Saunders, 2013)
Safely and effectively perform regional nerve blocks with Atlas of Ultrasound-Guided Regional Anesthesia, 2nd Edition. Using a wealth of step-by-step videos and images, Dr. Andrew T. Gray shows you how to use the latest methods to improve the success rate of these techniques.